Optimizing Project Performance by Applying the Crashing Method to Road Construction Project - Pramudya Febryanti Dewi; Zetta Rasullia Kamandang (Universitas PGRI Semarang, 2023)
In the implementation of projects, various obstacles are often encountered which cause delays which have an impact not only on the duration of implementation but also on the costs incurred. These constraints can be in the form of a lack of resources, weather factors to social factors. Thus, it is necessary to accelerate and optimize what can be done to overcome the delay. As well as efficient resource management. One of the acceleration methods that can be used is the Crashing method. One of them is the application of the crashing method to the Ringinrejo - BTS road construction project. Regency. Malang STA 2+350 – 6+300 which experienced delays in its implementation. After analyzing the remaining work, the duration of the remaining work was 273 days or completed on December 31, 2022. In the initial planning, the project was scheduled for completion on October 3, 2022, so based on this, the project experienced a delay of 89 days. The total minimum fee that must be incurred is IDR 1,524,960.00 with an additional fee of IDR 21,180,000.00 per day. Daily productivity for ordinary excavation works, which was originally 303.20 m³/hour, increased to 909.59 m³/hour. For daily productivity on ordinary embankment work which was originally 371.92 m³/hour to 743.84 m³/hour and productivity on road construction work which was originally 330.91 m³/hour to 661.81 m³/hour. After the acceleration using the crashing analyzing method on existing critical paths, it is known that the duration of project implementation which was originally 273 days became 184 days by adding the number of heavy equipment. with an additional fee of IDR 1,524,960,000